2012
DOI: 10.2169/internalmedicine.51.8728
|View full text |Cite
|
Sign up to set email alerts
|

Rapidly Progressive Respiratory Failure in Mixed Connective Tissue Disease: Report of an Autopsy Case

Abstract: A 64-year-old woman presented with exertional dyspnea. The case was diagnosed as mixed connective tissue disease (MCTD) due to presence of swollen fingers, Raynaud's phenomenon, muscle weakness, positive anti-U1RNP antibody, pericarditis and interstitial pneumonia. Although the histology from a transbronchial lung biopsy (TBLB) indicated organizing pneumonia, corticosteroid therapy was postponed for two months at the patient's request. She died 8 weeks later from acute progressive interstitial pneumonia in spi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
17
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(20 citation statements)
references
References 16 publications
(12 reference statements)
3
17
0
Order By: Relevance
“…The initial, but not always reliable, description of MCTD as a benign disease that transforms into other well known autoimmune disorders has limited its recognition during the study of SLE and other cohorts of autoimmune patients (Sharp et al, 1972;Tan et al, 1982;Hochberg et al, 1997;Lundberg, 2005;Petri et al, 2012;Shi et al, 2012). Recent studies have shown lung disease seems to be specifically associated with MCTD but not SLE patients (Shirai et al, 2012;Watanabe et al, 2012;Gunnarsson et al, 2013). By contrast, renal disorders have long been a characteristic prevalent in SLE but not the MCTD population (Everett and Harrell, 1956;Natali et al, 1972;Cavagna et al, 2013;Lin et al, 2013).…”
Section: Mixed Connective Tissue Disease (Mctd) Is One Of the Most Comentioning
confidence: 99%
See 4 more Smart Citations
“…The initial, but not always reliable, description of MCTD as a benign disease that transforms into other well known autoimmune disorders has limited its recognition during the study of SLE and other cohorts of autoimmune patients (Sharp et al, 1972;Tan et al, 1982;Hochberg et al, 1997;Lundberg, 2005;Petri et al, 2012;Shi et al, 2012). Recent studies have shown lung disease seems to be specifically associated with MCTD but not SLE patients (Shirai et al, 2012;Watanabe et al, 2012;Gunnarsson et al, 2013). By contrast, renal disorders have long been a characteristic prevalent in SLE but not the MCTD population (Everett and Harrell, 1956;Natali et al, 1972;Cavagna et al, 2013;Lin et al, 2013).…”
Section: Mixed Connective Tissue Disease (Mctd) Is One Of the Most Comentioning
confidence: 99%
“…Second, the concept of MCTD has clinical relevance since malfunction of vital organs has been reported to be prevalent in this syndrome when compared to SLE, for example (Everett and Harrell, 1956;Natali et al, 1972;Shirai et al, 2012;Watanabe et al, 2012;Gunnarsson et al, 2013). Third, new classification rules with significant power to distinguish between SLE and MCTD patients need to be developed given that available classification criteria sets were designed to identify either SLE or MCTD subjects but not to segregate between these two autoimmune disorders (Sharp, 1987;Kasukawa et al, 1988;Kahn et al, 1991;Amigues et al, 1996;Hochberg et al, 1997;Petri et al, 2012).…”
Section: Mixed Connective Tissue Disease (Mctd) Is One Of the Most Comentioning
confidence: 99%
See 3 more Smart Citations